Czarne dziury, białe plamy: w poszukiwaniu historii ukraińskiego eseju literackiego - Kotyńska, Katarzyna (Slavia Occidentalis, 2011)
The article is the reflexion on the situation of the Ukrainian literary essay. The author pays attention to the fact that the literary essay flourished in Ukraine in the 1990s. This information inspires the author to inquire into the origins of this phenomenon and the history of the Ukrainian essayistics, so far poorly recognized and examined.